Essential oils in the management of soft rot of kale in the brazilian semiarid region (Bioscience Journal, 2020)
The aim of this study was to analyze the effect of essential oils on the control of soft rot of kale. Clove essential oil at 0.25%, lemongrass and palmarosa essential oils at 0.5%, melaleuca and orange essential oils at 0.75%, bergamot, rosemary, sage and ginger essential oils at 1% were evaluated for the in vitro inhibition of Pectobacterium carotovorum subsp. brasiliensis (Pcb) and control of soft rot of kale, sprayed 72 hours before or seven hours after inoculation. Clove, citronella, bergamot, rosemary, palmarosa, sage, melaleuca, and lemongrass oils completely inhibited the growth of Pcb. Lemongrass oil (0.5%) caused 0% of disease incidence (INC), providing 100% of disease control in both periods of inoculation. Clove oil (0.25%) showed a lower INC (25%) when applied after inoculation, providing a control percentage of 71.42%. The lemongrass and clove essential oils were analyzed by GC/FID (Gas Chromatography – Flame Ionization Detector) and by GC/MS (Gas Chromatography /Mass Spectrometer). The major components were eugenol (91,9%) for clove oil and citral, isometric mixture of neral (34,1%) and geranial (42,9%) for lemongrass oil. The Minimum inhibitory concentration (MIC) of lemongrass, clove oils and their major components (citral and eugenol, respectively) was determined by using a broth macrodilution technique, as well as they were evaluated at different concentrations on the control of soft rot of kale, sprayed according descriptions above. The MIC was 0.03125% for citral, and 0.0625 and 0.125% for lemongrass and clove oils, respectively. Eugenol didn't show MIC. Lemongrass oil at 0.125% (post-inoculation) and citral at 0.125% (pre and post-inoculation) provided the highest percentages of disease control (33.33, 50, and 100%, respectively). Clove oil at 0.125% (post-inoculation) showed better effectiveness than eugenol (0.25%), providing a percentage of disease control of 16.67%. Lemongrass and clove essential oils were the most effective in control of soft rot of kale, suggesting that these oils have a potential to be used as antibacterial agents.